Anxiolytic effects of acute and maintenance ketamine, as assessed by the Fear Questionnaire subscales and the Spielberger State Anxiety Rating Scale. (February 2021) - Truppman Lattie, Dylan; Nehoff, Hayley; Neehoff, Shona; Gray, Andrew; Glue, Paul
Background: Ketamine has rapid anxiolytic effects in treatment-resistant obsessive compulsive, post-traumatic stress, generalised anxiety and social anxiety disorders. Objectives: This study aimed to assess changes following acute and maintenance ketamine therapy on the Fear Questionnaire (FQ) subscales and the Spielberger State Anxiety Inventory (SSAI). Methods: This secondary analysis used data from a mixed open-label and double-blinded placebo-controlled study. A total of 24 patients received short-term ascending subcutaneous doses of ketamine and were then eligible to enter a 3-month maintenance phase of 1 mg/kg ketamine dosed once or twice weekly. FQ and SSAI data were analysed using mixed models to identify between-dose differences and to describe trends during maintenance. Results: Acute ketamine dosing showed a rapid dose-related reduction in all three FQ subscales (agoraphobia, social phobia and blood-injury phobia) and in the SSAI. A progressive decrease in pre-dose rating-scale scores was evident during the 3 months of maintenance therapy. Conclusions: Ketamine demonstrated dose-related improvements in all FQ subscales and in the SSAI. Both scales appear to be suitable tools to assess the anxiolytic effects of ketamine in patients with treatment-resistant anxiety. Furthermore, ketamine appears to have broad, dose-related anti-phobic effects. These findings raise the possibility that ketamine may have therapeutic potential in the treatment of other phobic states, such as specific phobia.